Historical And Pedagogical Foundations of Improving the Professional and Legal Competencies of Youth of Eastern Thinkers (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
This article focuses on the idea that education and education of young people, as well as the idea of vocational training, are central to the teaching of Eastern thinkers.